ANALYSIS OF EMPLOYEE PERFORMANCE FACTORS OF MAMUJU REGENCY TRADE OFFICE - Wardiman Rasid; Nur Fajariani; Jamaludin Kamarudin (Jurnal Ekonomi, 2023)
This research conducted at the Office of Trade Department in Mamuju Regency aimed to analyze the factors influencing employee performance. The study spanned two months from March to June 2023, involving both qualitative and quantitative data sources. Findings indicate that leadership style, discipline, and motivation significantly impact employee performance. Effective leadership, high discipline levels, and strong work motivation enhance employee performance. Consequently, improving these factors should be a strategic focus for organizations seeking performance enhancement